Surface Engineering of Fluoropolymer Films via the Attachment of Crown Ether Derivatives Based on the Combination of Radiation-Induced Graft Polymerization and the Kabachnik–Fields Reaction - Omichi, Masaaki (Polymers (Basel), 2019)
In this manuscript, we present the successful attachment of crown ether moieties onto fluoropolymer surfaces, via the combination of radiation-induced graft polymerization and a subsequent surface Kabachnik–Fields three-component reaction. The obtained crown ether-tethered fluoropolymer films exhibited an ammonium cation capturing ability, owing to the host–guest interactions (i.e., hydrogen bonding) between the surface-anchored crown ethers and the guest ammonium cations.